Ex vivo expansion of hematopoietic stem cells derived from umbilical cord blood in rotating wall vessel. - Liu, Y; Liu, T; Fan, X; Ma, X; Cui, Z (2006)
Expansion of umbilical cord blood mononuclear cells (UCB MNCs) was carried out in a rotating wall vessel (RWV) bioreactor and tissue culture flasks (T-flasks) in serum-containing medium supplemented with relatively low doses of purified recombinant human cytokines (5.33 ng/ml IL-3, 16 ng/ml SCF, 3.33 ng/ml G-CSF, 2.13 ng/ml GM-CSF, 7.47 ng/ml FL and 7.47 ng/ml TPO) for 8 days. The cell density, pH and osmolality of the culture medium in the two culture systems were measured every 24h. Flow cytometric assay for CD34+ cells was carried out at 0, 144 and 197 h and methylcellulose colony assays were performed at 0, 72, 144 and 197 h. The pH and osmolality of the medium in the two culture systems were maintained in the proper ranges for hematopoietic stem cells (HSCs) and progenitors culture. The RWV bioreactor, combined with a cell-dilution feeding protocol, was efficient to expand UCB MNCs. At the end of 200 h culture, the total cell number was multiplied by 435.5+/-87.6 times, and CD34+ cells 32.7+/-15.6 times, and colony-forming units of granulocyte-macrophage (CFU-GM) 21.7+/-4.9 times. While in T-flasks, however, total cells density changed mildly, CD34+ cells and CFU-GM decreased in number. It is demonstrated that the RWV bioreactor can provide a better environment for UCB MNCs expansion, enhance the contact between HSCs and accessory cells and make the utilization of cytokines more effective than T-flask.